2021
DOI: 10.1590/1983-1447.2021.20200012
|View full text |Cite
|
Sign up to set email alerts
|

Health functional literacy and adherence to antiretroviral therapy in people living with HIV

Abstract: Objective: To verify the relationship between adherence to antiretroviral therapy and Functional Health Literacy. Methods: Cross-sectional study, carried out in the Specialized Care Service in 2019, using questionnaires about adherence to treatment and Functional Health literacy people living with human immunodeficiency virus. The LFS questionnaire has questions about numerical and text interpretation skills and the adherence questionnaire addresses how to use antiretrovirals. Viral load was verified by analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
2
0
6
Order By: Relevance
“…Regarding compliance with ART throughout HIV treatment, the association between greater HL and strict compliance with drug therapy was found in this study, in the same way that the findings of a study carried out in the city of São Paulo showed that the lower the HL, the greater the difficulties in complying with treatment (22) . Health professionals have an essential role in health education and in the promotion of measures that support compliance, given that the central focus of public policy to reduce new cases of HIV infection is viral load remission, only being possible through compliance with ART.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding compliance with ART throughout HIV treatment, the association between greater HL and strict compliance with drug therapy was found in this study, in the same way that the findings of a study carried out in the city of São Paulo showed that the lower the HL, the greater the difficulties in complying with treatment (22) . Health professionals have an essential role in health education and in the promotion of measures that support compliance, given that the central focus of public policy to reduce new cases of HIV infection is viral load remission, only being possible through compliance with ART.…”
Section: Discussionsupporting
confidence: 88%
“…No entanto, mesmo com a distribuição gratuita dos antirretrovirais, a adesão ao tratamento não é universal por fatores como a desigualdade social e econômica 17 . Nesse sentido, assim como em outros estudos 15,22 , identificou-se uma alta taxa de participantes com adesão insuficiente a terapia medicamentosa, ainda que a grande maioria refira ingerir até três medicamentos por dia, fator já comprovado em outro estudo, no qual pacientes que utilizam até três medicações têm maiores graus de adesão medicamentosa 30 .…”
Section: Discussionunclassified
“…Outro fator importante para uma boa adesão medicamentosa é o conhecimento e compreensão pelos pacientes sobre a enfermidade e o tratamento em questão 12 . De encontro a isso, há na literatura uma comprovada associação entre o baixo Letramento em Saúde (LS) e a baixa adesão medicamentosa, de tal forma que um interfere diretamente sobre o outro 15 . Isso significa dizer que, a limitação em habilidades básicas de leitura e escrita em pessoas vivendo com HIV/AIDS, prejudica além da obtenção de informações de saúde, a aplicação desse conhecimento em uma série de atividades prescritas, como a adesão à medicação 31 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Com relação à adesão à TARV ao longo do tratamento do HIV, a associação entre maior LS e adesão estrita à terapia medicamentosa foi encontrada neste estudo, do mesmo modo que os achados de um estudo realizado no município de São Paulo mostrou que, quanto menor o LS, maiores as dificuldades de aderir ao tratamento (22) . Os profissionais de saúde têm um papel imprescindível na educação em saúde e na promoção de medidas que apoiem a adesão, tendo em vista que o foco central da política pública de redução de novos casos de infecção por HIV é a remissão da carga viral, só sendo possível por meio da adesão à TARV.…”
Section: Discussionunclassified